Integritas Akademik pada Mahasiswa Kesehatan di Perguruan Tinggi Swasta - Embun Nadya; Mastina Mastina (LPPM STIKES KENDAL, 2020)
Background: principles embedded in academic integrity must be obeyed by students. However, in the field there are still many students who commit fraud or dishonesty in the academic environment. Globally there is also academic dishonesty committed by prospective teachers, students and others. students who tend to do dishonesty in the academic field will tend to do dishonesty in the world of work. Objective: to understand and describe academic integrity in students. Subject: 12 students. Method: descriptive-qualitative phenomenology approach, data collection using semi-structured interviews. Results: the research shows that students strongly uphold academic integrity values, with various understandings they express that integrity is a form of student responsibility and informants also explain the problems of academic integrity that are often encountered, many of students still commit academic cheating and the most often is breaking a norm of honesty, many of the students are still cheating on exams, doing plagiarism and so on. Conclusion: by instilling the value of self-integrity in the academic environment, students are able to become good personal and mature for the future and become professional in their fields.